Ancient Greece : the definitive visual history - Merritt, Ed (DK Classic History, 2025)
"Spanning more than 3,000 years, Ancient Greece explores the tumultuous history of this glorious empire in vivid detail--from its Minoan and Mycenaean origins to the apogee of the warring city-states of Athens and Sparta, and from the death of its most charismatic leader, Alexander the Great, to its ultimate defeat by Rome."--Provided by publisher.